Assessing the Economic Impact of Competition Law Enforcement on Market Efficiency in Indonesia - Fadhel Arjuna Adinda; Rosyidi Hamzah (The Indonesian Journal of Economic Analysis of Law, 2026)
This paper analyzes the economic consequences of competition law enforcement on market efficiency in Indonesia. Competition law plays a critical role in preventing monopolistic practices, abuse of dominant positions, and anti-competitive agreements that may harm consumer welfare. Employing the law and economics approach, the study investigates whether enforcement actions undertaken by regulatory authorities contribute to efficient market outcomes. The research utilizes normative legal analysis supported by economic theories of market competition and welfare economics. The findings reveal that effective competition law enforcement enhances market efficiency by reducing barriers to entry, encouraging innovation, and lowering prices for consumers. However, excessive regulatory intervention may generate enforcement costs and uncertainty that negatively affect business activities and investment incentives. The study further explores the relationship between legal sanctions and deterrence effects, demonstrating that proportionate sanctions can reduce anti-competitive behavior while preserving economic productivity. From an economic analysis of law perspective, the effectiveness of competition law should be measured not only by legal compliance but also by its impact on social welfare and resource allocation. The paper recommends improving institutional capacity, enhancing transparency in enforcement procedures, and adopting economic evidence in competition law assessments. These measures can strengthen the role of competition law in promoting sustainable economic growth and fair market competition in Indonesia.